Farming Technology, Farmers Income and Livelihood Diversification in Kulon Progo - Gunardo, RB (Forum Geografi, 1999)
The objetive of this research were conducted in Kulon Progo Regency were to know how far utilization of farm technology (hand tracctor, tresher, benguk arver, and cassava rapier) will inreasing income farmer and works diversification on different topography and accesibility. The data included primary and secondary data. The primary data were collected from respondents by filling questionnaires, while the seondary data were collected from the governmental officer. Region samples are Lendah sub regency which low land plain area, Sentolo sub regency which hilly area, and KalibawangÂ sub regency which mountain range area. Respondents sample was taken by snow ball sampling, who utilized of farm technology and they are 58 respondents from low land plain area, 38 respondents from hilly area, and 38 respondents from mountai range area. The data were processed by using computer, while hypothesis was tested by crosstab and hi quadrate to compare result of research in the three different topography areas. The result of the research shows that there are difference significant utilization of farm technology aording to the topography bakground. Hand tractors and tresher are muchÂ utilized in the hilly areas, benguk carvers are much utilized in the low land plain areas, and cassava raspiers are much utilized in the mountain range areas. They arenât difference signifiant the utilization of farm technology aording to accesibility. The low land plain areas and the hilly areas produce same activities, while the mountain range areas produce only four kind of same ativities. Diversification of works in the hilly areas absorbed a lot of manpower than those and the rest areas. Income generating from the utilization of farm technology in the hilly areas is more than that in the rest areas.